Classroom-Based Gamification to Improve Students’ Arabic Speaking Skills: A Classroom Action Research at Smp Al-Faruqi - Syafia Imarani; Yusriyah; Jihan Padilah Dalimunthe; Pitroh Aulia Putri; Nurul Hidayati Rusmar; Susilawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This classroom action research was conducted to address the low Arabic speaking performance of class VIII.3 students at SMP Al-Faruqi. Preliminary observation showed that students had limited vocabulary mastery, low confidence in speaking Arabic, and limited participation in oral classroom activities. Although gamification has been widely discussed in language learning, its classroom-based implementation for improving mahārah al-kalām at the junior high school level remains underexplored. Therefore, this study aimed to describe the implementation of a classroom-based gamification strategy and to examine its contribution to improving students’ Arabic speaking skills. The study involved 24 students and was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through classroom observation, speaking tests, and documentation. The gamification strategy was implemented through four games: matching card, sentence completion, flip bottle, and guess the card. The data were analyzed descriptively by calculating the mean score and the percentage of classical mastery. The findings showed that students’ speaking achievement improved from Cycle I to Cycle II. In Cycle I, the mean score was 65.33, with 9 of 24 students achieving mastery and classical mastery reaching 37.5%. After improving the game instructions, task sequence, feedback, and reward system in Cycle II, the mean score increased to 81.33, with 20 of 24 students achieving mastery and classical mastery reaching 83.33%. The study contributes to Arabic learning by showing that simple, low-cost classroom games can provide structured oral practice and create a more active speaking environment.